Uganda : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Uganda reached the completion point under the enhanced HIPC Initiative on May 1, 2000. Staff is of the view that all criteria are met, and recommends that the Board determine that Uganda qualifies for immediate debt relief under the MDRI.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: HIPC Assessment; HIPC Assistance; PAF Expenditure; PP; Uganda's Poverty Eradication Action Plan; Uganda